Improvement of the alcohol content and an investigation of fermentation and maturation temperatures on the chemical and sensory characteristics of unpasteurised starter culture-based marula fruit wine - Mapheto, Ramatsobane Phangisile Robyn (My University, 2024)
Marula fruit wine is an alcoholic beverage that is produced through fermentation of marula fruit juice. The traditional marula fruit wine has a low alcohol content and spoils quickly. This study investigated the production of a high alcohol wine through starter culture-based fermentation of unpasteurised marula fruit juice. The influence of varying fermentation and maturation temperatures (15 °C and 25 °C) on chemical and sensory properties were explored. Selected chemicals, nutritional content and sensory characteristics were evaluated. The fermentation rate at 25 °C surpassed that at 15 °C, with wines reaching 1.0 °Brix in 10 days and 30 days, respectively. Alcohol content increased gradually and reached 12% as sugar got utilised. A pH of 3.44 – 3.88 deterred spoilage microorganisms yet Bacillus species, commonly found in soil and associated with winemaking, were observed in the wines at 15 °C and 25 °C post fermentation. Evaluation of organic acids revealed citric acid dominance (3.28 – 5.70 g/L), along with malic acid (2 – 6 g/L) and low levels of acetic acid (< 2.1 g/L), contributing to desirable sensory characteristics. While temperature variations did not significantly influence higher alcohols, levels at 25 °C were higher than at 15 °C. Mineral concentrations fell below dietary recommendations, with notable potassium and sodium quantities. Protein content ranged from 7.5 to 11 μg/mL. The antioxidant, vitamin C, ranged from 96.6 – 128.7 μg/mL in the 25 – 4 °C wine during the storage phase. The interactions of the chemicals and yeasts contributed to the sensorial characters of the wine. The wine fermented and stored at 15 °C, i.e., 15 – 15 °C and 15 – 4 °C demonstrated to be the most appreciated for taste. This could be attributed to the residual sugar content and higher alcohols for its sweetness and fruity taste. The findings demonstrated that varying temperature did not influence most of the selected nutritional content. Additionally, 25 °C should be used to initiate fermentation, 15 °C for maturation and finally 4 °C for aging to balance the rate of fermentation progression and the production of good wine character. Despite a general understanding of the impact of temperature on flavour development and chemical contribution, the full extent of its influence remains a subject of ongoing exploration.
Thesis (M.Sc. (Microbiology)) -- University of Limpopo, 2024
Keywords: Alcoholic beverage; Traditional marula fruit wine; Alcohol content; Fermentation; Sclerocarya birrea; Wine and wine making